The effect of snakehead fish (Channa striata) snacks on nutrition outcomes of adolescence female at risk of chronic energy deficiency - Annasari Mustafa; Dwie Soelistyorini; Astutik Pudjirahaju; Yohanes Kristianto; Selsabilla Aulia Wardhani; Puput Dewi Safitri (Jurnal Gizi Klinik Indonesia)
Background: Chronic energy deficiency (CED) is still prevalent in Indonesia, affecting 36.3% adolescent females. The high protein content in snakehead fish presents a promising solution to address the problem.